الإتجاهات العلمية وعلاقتها بالتحصيل الدراسي لدى تلاميذ السنة الأولى ثانوي جذع مشترك علوم وتكنولوجيا - بدادي، زهية, دحة، عائشة (جامعة الوادي university of Eloued, 2020)
الملخص:هدفت دراستنا الحالية إلى الكشف عن العلاقة بين الإتجاهات العلمية نحو مادة العلوم والتحصيل الدراسي لدى تلاميذ السنة الأولى ثانوي جذع مشترك علوم وتكنولوجيا. وقد تم الإعتماد في هذه الدراسة على المنهج الوصفي الإرتباطي لإيجاد العلاقة للظاهرة المدروسة، أما لجمع البيانات من الميدان فقد إعتمدنا على آداة الإستبيان والذي تكون من 38 بندا فيما تم أخذ تحصيل التلاميذ لمادة العلوم في الفصل الأول، وقد تم إجراء الدراسة الميدانية على عينة مكونة من 100 تلميذ تم إختيارهم بطريقة قصدية عشوائية، فيما تم تطبيق الإستبيان على جميع أفراد العينة، وبعد تحليل النتائج تم التوصل إلى أنه توجد علاقة ذات دلالة إحصائية بين الإتجاهات العلمية نحو مادة العلوم والتحصيل الدراسي لدى تلاميذ السنة الأولى ثانوي جذع مشترك علوم وتكنولوجيا، أما فيما يخص الفرضيات الجزئية تم التوصل في الفرضية الجزئية الأولى على أنه لا توجد فروق ذات دلالة إحصائية في الإتجاهات العلمية نحو مادة العلوم تُعزى لمتغير الجنس(ذكور_إناث) والفرضية الجزئية الثانية بينت على أنه توجد فروق ذات دلالة إحصائية في الإتجاهات العلمية نحو مادة العلوم تُعزى لمرتفعي ومنخفضي التحصيل Résumé :فرنسية أو انجلزية Our current study aimed to reveal the relationship between scientific trends towards the subject of science and academic achievement for first year secondary school students with a common trunk science and technology. This study relied on the relational descriptive approach to find the relationship to the studied phenomenon. As for collecting data from the field, wa relied on the questionnaire tool which consisted of 38 items, while students achievement of science was taken in the first semester. The field study was conducted on a sample consisting of 100 students were randomly chosen, with the questionnaire applied to all members of the sample, and after analyzing the results it was concluded that there is a statistically significant relationship between scientific trends towards the subject of science and academic achievement for first year secondary school students with a common trunk of science and technology, as for the partial hypotheses, it was reached in the first partial hypothesis that there are no statistically significant differences in the scientific directions towards the subject of science due to the gender variable (male_female) and the second partial hypothesis indicated that threr are statistically significant differences in the scientific attitudes towards the subject of science attributed to high low achievement.
دراسة ميدانية بثانوية الشهيد بوضياف بوضياف تغزوت
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الإتجاهات العلمية، التحصيل الدراسي; Tendances scientifiques, réussite scolaire; Tendances scientifiques, réussite scolaire